Bacterial community structure across environmental gradients in permafrost thaw ponds: methanotroph-rich ecosystems - Crevecoeur, Sophie; Vincent, Warwick F.; Comte, Jérôme; Lovejoy, Connie (Frontiers in Microbiology, 2015)
Permafrost thawing leads to the formation of thermokarst ponds that potentially emit CO2 and CH4 to the atmosphere. In the Nunavik subarctic region (northern Quebec, Canada), these numerous, shallow ponds become well stratified during summer. This creates a physico-chemical gradient of temperature and oxygen, with an upper oxic layer and a bottom low-oxygen or anoxic layer. Our objective was to determine the influence of stratification and related limnological and landscape properties on the community structure of potentially active bacteria in these waters. Samples for RNA analysis were taken from ponds in three contrasting valleys across a gradient of permafrost degradation. A total of 1296 operational taxonomic units were identified by high-throughput amplicon sequencing, targeting bacterial 16S rRNA that was reverse transcribed to cDNA. β-proteobacteria were the dominant group in all ponds, with highest representation by the genera Variovorax and Polynucleobacter. Methanotrophs were also among the most abundant sequences at most sites. They accounted for up to 27 % of the total sequences (median of 4.9 % for all samples), indicating the importance of methane as a bacterial energy source in these waters. Both oxygenic (cyanobacteria) and anoxygenic (Chlorobi) phototrophs were also well represented, the latter in the low oxygen bottom waters. Ordination analyses showed that the communities clustered according to valley and depth, with significant effects attributed to dissolved oxygen, pH, dissolved organic carbon and total suspended solids. These results indicate that the bacterial assemblages of permafrost thaw ponds are filtered by environmental gradients, and are complex consortia of functionally diverse taxa that likely affect the composition as well as magnitude of greenhouse gas emissions from these abundant waters.